TERRITORY OF THE MARACATUS-NAÇÃO OF PERNAMBUCO: PRELIMINARY INTERPRETATION - Ferreira, Cleison Leite; Anjos, Rafael Sanzio Araújo dos (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
The “Maracatu-Nação” is an important cultural expression found in Pernambuco, Brasil, in the cities of Recife, Olinda, Jaboatão dos Guararapes and Igarassu. It was creatade by people of African origin from the elections and coronations of Kings and Queens chosen from lay brotherhoods that brought together a wide ethnic diversity between the sixteenth and nineteenth centuries.